برصغیر اور عالمِ عرب کے انقلابی شعرا کا فکری و نظریاتی تقابل: علامہ محمد اقبال اور ابو القاسم الشابی: An Intellectual and Ideological Comparison of Revolutionary Poets of the Subcontinent and the Arab World: Allama Muhammad Iqbal and Abu al-Qasim al-Shabbi - Dr Sadia Nasrullah; Dr. Muhammad Akram Nizami (Al-Amīr Research Journal for Islamic Studies, 2025)
Generally, comparative studies of poets or writers belonging to the same language aim to establish the intellectual or artistic superiority of one over the other. However, a comparative study of literature across different languages serves a broader and more meaningful purpose. Such studies not only present a clear understanding of literary history, linguistic features, stylistic tendencies, emotions, and modes of expression of different languages, but also provide valuable insights into the social attitudes, religious beliefs, political consciousness, social structures, and intellectual orientations of the societies to which these writers belong. Moreover, comparative literary analysis helps determine the social impact of literature and the extent of a writer’s influence within their respective cultures. In a wider perspective, it highlights the intellectual and ideological affinities or divergences among different languages, nations, and civilizations by examining both similarities and differences. The present article offers an intellectual and ideological comparison between the poet of the East, Allama Muhammad Iqbal, and the renowned Arab poet, Abu al-Qasim al-Shabbi. It seeks to analyze selected aspects of similarity and difference in their thought, highlighting how both poets responded to the socio-political conditions of their time through their literary expression. Keywords: Comparative Literature, Intellectual Comparison, Ideological Thought, Allama Muhammad Iqbal, Abu al-Qasim al-Shabbi, Revolutionary and Reformist Poetry